Large-scale implementation of IPM in basmati rice - Tanwar, R K; Singh, S P; Kanwar, Vikas (Indian Farming, 2018)
Adoption of IPM technology empowered the farmers in followingways They understood the role of crop management practices in IPM (like judicious use of fertilizers, growing of Sesbania for greenmanuring). They are able to distinguish between harmful and beneficial insects (earlier all insects were considered as pests by them). They are able to identify major diseases (there was confusion about identity). Farmers of these villages now understand the role of monitoring and concept of ETL and carry out need based application of pesticides (earlier, mere presence of any insect or disease was enough to go for pesticide application). Decision making for release of parasitoids/ pesticide application (prior to IPM programme, farmers were applying the pesticides indiscriminately). Farmers now adopt only spot application.